Cognitive Styles and Learning Strategies on Smart Learning Environment Effectiveness in Secondary School Mathematics Achievement - Temitope Oteyola; Kehinde Oluyemisi Akintitan (ETDC: Indonesian Journal of Research and Educational Review, 2026)
The study investigated the influence of cognitive styles on the effect of locally developed smart learning environment on students' academic achievement in Mathematics in public secondary schools in Osun State, Nigeria. It also investigated the influence of students' learning style preference on the effect of the smart learning environment on students' academic achievement in the subject. The study adopted the pretest posttest control group quasi experimental design. The population of the study comprised all senior secondary school students in Osun State, Nigeria. One hundred and fifty SS II students were selected using a multistage sampling procedure. Mathematics Achievement Test (MAT), Cognitive Style Inventory (CSI), and Learning Style Inventory (LSI) were used for data gathering. Analysis of data showed no significant difference (F (1,107) = 0.06; p = 0.81) in the influence of cognitive styles on the effect of the smart learning environment. The results showed a significant difference in the influence of learning strategies on the effect of the smart learning environment on students' academic achievement in Mathematics (F (2,143) = 4.933; p = 0.008). The study concluded that a well-designed smart learning environment can enhance students' academic achievement in Mathematics irrespective of their cognitive styles, preferred learning style and sex.